2001
DOI: 10.1104/pp.125.1.447
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure and Expression of a 24-kD Vacuolar Protein (VP24) Precursor in Anthocyanin-Producing Cells of Sweet Potato in Suspension Culture

Abstract: A 24-kD vacuolar protein (VP24) accumulates abundantly in intravacuolar pigmented globules in anthocyanin-containing sweet potato (Ipomoea batatas) cells in suspension culture. A cDNA clone encoding VP24 was isolated from a cDNA library constructed from light-irradiated suspension-cultured cells. Sequence analysis revealed that a 2.9-kbp VP24 cDNA encodes a protein of 893 amino acid residues with a molecular mass of 96.3 kD. According to the deduced amino acid sequence of VP24 cDNA, VP24 is probably synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…It is proposed that glutathione-S-transferase-like proteins such as maize BZ2 (Marrs et al, 1995), petunia AN9 (Mueller et al, 2000), and Arabidopsis TT19 (Kitamura et al, 2004) deliver their flavonoid substrates to the transporter, such as the maize multidrug resistance-associated protein (MRP)-type transporter ZmMRP3 (Goodman et al, 2004) or the Arabidopsis multidrug and toxic compound extrusion transporter TT12 . In sweet potato, it has been suggested that VP24 precursor protein is involved in vacuolar transport and/or accumulation of anthocyanin (Nozue et al, 1997;Xu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that glutathione-S-transferase-like proteins such as maize BZ2 (Marrs et al, 1995), petunia AN9 (Mueller et al, 2000), and Arabidopsis TT19 (Kitamura et al, 2004) deliver their flavonoid substrates to the transporter, such as the maize multidrug resistance-associated protein (MRP)-type transporter ZmMRP3 (Goodman et al, 2004) or the Arabidopsis multidrug and toxic compound extrusion transporter TT12 . In sweet potato, it has been suggested that VP24 precursor protein is involved in vacuolar transport and/or accumulation of anthocyanin (Nozue et al, 1997;Xu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Genes harboring KPRPR(S/T) F-like motif correspond to the genes of the N09 subgroup in Figure 4C. transport and/or trapping (Nozue et al, 1997;Xu et al, 2001).…”
Section: Tissue-specific Expression Of Genes Involved In Anthocyanin mentioning
confidence: 99%
“…In sweet potato (Ipomea batatas), carnation (Dianthus caryophyllus), and lisianthus (Eustoma grandiorum), AVIs appear to lack surrounding membranes and instead consist of a protein matrix or thread-like structures (Small and Pecket, 1982;Nozue et al, 1993;Markham et al, 2000;Zhang et al, 2006;Conn et al, 2010). Besides anthocyanins, AVIs have been reported to contain a metalloprotease called VP24 in sweet potato (Nozue et al, 1997(Nozue et al, , 2003Xu et al, 2001) and tonoplast membrane lipids in grapevine cultured cells (Conn et al, 2010). In grapevine cell cultures, AVIs are enriched in acylated anthocyanins (Conn et al, 2003), suggesting that AVIs may sequester specific anthocyanin species.…”
Section: Introductionmentioning
confidence: 99%
“…The structure has been shown to be, in part, comprised of a hydrophobic proteinaceous matrix which colocalises with anthocyanins. A component of the AVIs was determined to be a 24-kDa protein (VP24), which has been purified and localised to the AVIs by immuno-localisation (Nozue et al , 1997 and the gene cloned (Xu et al 2001).…”
Section: Introductionmentioning
confidence: 99%